Analysis of the Impact of Liquidity Ratio, Leverage, Profitability, and Activity on Financial Distress in Transportation Companies Listed on the Indonesia Stock Exchange from 2019 to 2021 - Bessie, Florance Angelina; Prasetyanta, Agus; Kaloeti, Ade Kristianus (EQUILIBRIUM - Jurnal Bisnis dan Akuntansi, 2025)
The purpose of this study is to test whether the ratio of liquidity, leverage, profitability, and activity affects financial distress in transportation companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This research is a quantitative study, the population in this study is 30 transportation companies and obtained a sample of 15 companies. The data source in this study is secondary data, namely the financial reports of transportation companies obtained through the official website of the Indonesia Stock Exchange. The analytical tools used are descriptive statistical analysis, classical assumption test, simple linear regression, T test, multiple linear regression, and F test. The results show that liquidity and profitability partially have a significant positive effect on financial distress, leverage partially has a significant negative effect on financial distress, while activity partially does not have a significant effect on financial distress in transportation companies. The results of other studies show that liquidity, leverage, profitability, and activity simultaneously have a significant effect on financial distress in transportation companies on the Indonesia Stock Exchange for the 2019-2021 period.